Correlation of Pap smear and colposcopic finding with directed biopsy in detection of cervical neoplasm - Dr. Jigna Upadhyay; Dr. Sameep Garg (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: Cancer of uterine cervix is the most common genital tract malignancy. Pap smear though widely used screening test for cervical cancer has the disadvantage of low sensitivity. Colposcopy has higher sensitivity compared to Pap smear. Concurrent screening with Pap smear and colposcopy can overcome this problem.Aim: The aim of the study was correlation of Pap smear and colposcopic finding with directed biopsy in detection of cervical neoplasm. Methods: The Present study was conducted in the Department of Pathology, Gujarat Adani Institute of Medical Science, Bhuj, Kutch.During the study period in 57 symptomatic patient’s simultaneous Pap smear, colposcopic examination, followed by directed biopsy was performed. Data was recorded and analyzed. Results: In correlation between cytology and biopsy, sensitivity of cytology was 82.3%, specificity 96.9% and accuracy of 92%. In correlation between colposcopy and biopsy, sensitivity of colposcopy was 94.1%, specificity 87.8% and accuracy of 90%.Conclusion: High sensitivity in colposcopy as compared to cytology and high specificity in cytology as compared to colposcopy emphasizes the need for pairing these methods to achieve better results.